ANALISIS PENERAPAN MODEL PROBLEM BASED LEARNING PADA PELAJARAN IPAS KELAS IV DI SEKOLAH DASAR - Ashry, Tiara Nur; Sumarno, S; Nugroho, Aryo Andri; Handayaningsih, Susi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
The aim of this research is to understand the process of using the Problem Based Learning paradigm used by teachers in class IV science learning at SDN Pandeanlamper 04 Semarang. The method used by researchers is a qualitative descriptive method. The data collection method in this research uses observations and documented sheets. Students in class IV were divided into two groups: nine girls and sixteen boys. Based on the research results, the Problem Based Learning Model for class IV science and science lessons used at SDN Pandeanlamper 04 Semarang has been proven to be effective in learning science and can complete the five phases in PBL syntax. Researchers have accommodated that it can be concluded that students have been involved in problem solving and are able to learn using a problem-based learning model well.